Vulnerability Analyses of Structural Insulated Panels with OSB Skins Strengthened by Basalt Fiber Cloth Subjected to Windborne Debris Impact - Meng, Qingfei; Chen, Wensu; Hao, Hong (World Scientific Publishing Co. Pte. Ltd., 2018)
© 2018 World Scientific Publishing Company. In this study, numerical simulations are conducted with a verified model to develop damage threshold curves for structural insulated panels (SIPs) with OSB skins strengthened by basalt fiber cloth subjected to windborne debris impact. Numerical models of the SIP with OSB skins strengthened by basalt fibre cloth at the front or back side are developed by using LS-DYNA. The accuracy of the numerical model is verified by comparing numerical results with laboratory testing data. Using the verified numerical model, intensive simulations are conducted to examine the influence of various parameters, including thickness of basalt fiber, location of basalt fiber layer, bonding strength between the basalt fiber cloth and the OSB skin, on the dynamic responses of the SIP. The debris penetration or fracture of the strengthened SIP that creates an opening is defined as failure of the panel in this study. Empirical formulae are derived on the basis of the numerical results to predict the thresholds of penetration velocity and projectile mass that lead to failure of the SIP. The empirical formulae can be straightforwardly used to assess the performance of the SIP with OSB skins strengthened by basalt fiber cloth subjected to windborne debris impact.